Colonial Legacies and Gender Representation on Social Media's Muslim Fashion Brands in Indonesia - Baroroh, Hilma Erfiani; Anam, Haikal Fadhil; Kharisma, Mifta (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2025)
Despite the positive impacts, there are challenges in how Muslim fashion is digitally represented, particularly in how social media can unintentionally reinforce stereotypes or uphold Western beauty standards shaped by colonial legacies. Therefore, critical engagement is essential to ensure a more inclusive and unbiased portrayal. This study examines postcolonial and gender representations in Indonesian Muslim fashion brands on social media using a qualitative content analysis approach. The study analyses four Instagram accounts using an interpretive framework: @vanillahijab, @winonamodest, @hijabalila, and @nusseyba.id. By integrating postcolonial and gender theories, this research critically explores the influence of colonial discourse on hijab brands in the digital space. The findings reveal that these brands' social media platforms serve as a space for cultural reclamation, challenge traditional gender roles, and offer more diverse representations of Muslim women. However, many still reflect colonial narratives, particularly in promoting Westernized beauty ideals such as fair (white/light) skin, a thin, and a tall figure. Regarding gender representation, the content predominantly depicts women as professionals actively engaged in the workforce. These highlight the need for a more conscious and inclusive approach in digital Muslim fashion branding, encouraging brands to actively challenge colonial beauty norms and promote diverse representations that resonate with Indonesia's rich cultural and ethnic identities.